Understanding Preservice Teachers’ Reluctance to Use of Online Learning Platforms to Teach Individuals with Intellectual Disability - Udeme Samuel Jacob; Jace Pillay (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
This study investigated the reluctance among pre-service to adopt online learning platforms to teach students with intellectual disability. This study consisted of pre-service teachers. The qualitative phenomenological research method was used to examine pre-service teachers' reluctance to adopt online learning platforms to teach students with intellectual disabilities. In-depth interviews were conducted with pre-service teachers at the Faculty of Education, University of Ibadan. Seven respondents selected using a convenient sampling technique participated in the study; respondents were referred to as Participant 1 to Participant 7 for the purpose of anonymity. Collected data were transcribed and analysed using ATLAS.ti version 22, a computer-aided qualitative data analysis software. Based on participants' responses, four major themes were generated on the perception: opportunities to access various learning platforms, no special provision for learners with intellectual disability, the possibility of learning biases, and ineffective learning methods. Based on the evidence presented here, individuals with ID will not be able to access online learning platforms to the same degree as others within society.